When Training Becomes Incentive for Generative Living and Working Together in Organizations. Issue 5 (17th August 2016) - Frascaroli, Daniela; Gozzoli, Caterina; D'Angelo, Chiara
Abstract : This article has come about from two considerations: on one hand, living together in a work environment is becoming more and more challenging; on the other, training professionals at work represents a used and relevant action incentive in order to support and improve individual, group, and organizational development. In light of the fact that organizations are asking more and more complex questions, this work aims at developing a reflection on how adopting a certain perspective and educational method is particularly suitable to support the organization to achieve substantial outcomes, such as developing generative living and working together in organizations. In this article, we will analyze two illustrative cases, underlining evolution and learning process with a particular focus on the consequences of living and working together in organizations.